Upaya Pengelolaan Dan Pemanfaatan Dalam Air Limbah Domestik Tekstil Pencetakan Kain di PT X - Muhammad Alvando Rahmantio; Rizka Novembrianto (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The fabric printing industry makes a major contribution to various kinds of textile products, its by-products, liquid waste, require special attention in environmental management. Most of the liquid waste originating from the fabric printing industry consists of dyes, solvents and other processing chemicals. To prevent negative effects on water quality and the surrounding environment, managing this waste is very important. To achieve sustainability, advances in liquid waste processing technology are very important. The solution to reduce the impact of liquid waste from the fabric printing industry is an advanced purification process. PT. X to reduce polutan parameter such BOD, COD , TSS, Ammonia and Total Colidform by. 90%, 95%, 95%, 85%, 20%, 90% And meets the specified quality standards. Because the pH parameters still meet existing quality standards, processing is focused on reducing the organic parameters which are quite high. The results of the process will be used again for flushing activities in green open spaces and for washing operational vehicles.